PRD-Containing Virulence Regulators (PCVRs) in Pathogenic Bacteria - Rom, Joseph S.; Hart, Meaghan T.; McIver, Kevin S. (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial pathogens rely on a complex network of regulatory elements to adapt to hostile and nutrient-limiting host environments. The phosphoenolpyruvate phosphotransferase system (PTS) is a conserved pathway in bacteria that couples transport of sugars with phosphorylation to monitor host carbohydrate availability. A family of structurally homologous PTS-regulatory-domain-containing virulence regulators (PCVRs) has been recognized in divergent bacterial pathogens, including Streptococcus pyogenes Mga and Bacillus anthracis AtxA. These paradigm PCVRs undergo phosphorylation, potentially via the PTS, which impacts their dimerization and their activity. Recent work with predicted PCVRs from Streptococcus pneumoniae (MgaSpn) and Enterococcus faecalis (MafR) suggest they interact with DNA like nucleoid-associating proteins. Yet, Mga binds to promoter sequences as a homo-dimeric transcription factor, suggesting a bi-modal interaction with DNA. High-resolution crystal structures of 3 PCVRs have validated the domain structure, but also raised additional questions such as how ubiquitous are PCVRs, is PTS-mediated histidine phosphorylation via potential PCVRs widespread, do specific sugars signal through PCVRs, and do PCVRs interact with DNA both as transcription factors and nucleoid-associating proteins? Here, we will review known and putative PCVRs based on key domain and functional characteristics and consider their roles as both transcription factors and possibly chromatin-structuring proteins.